2010
DOI: 10.2344/0003-3006-57.3.96
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of Intravenous Sedation With Two Doses of Dexmedetomidine: 0.2 µg/kg/hr Versus 0.4 µg/kg/hr

Abstract: The present study investigated the physiologic and sedative effects between two different continuous infusion doses of dexmedetomidine (DEX). Thirteen subjects were separately sedated with DEX at a continuous infusion dose of 0.2 µg/kg/hr for 25 minutes after a loading dose of 6 µg/kg/hr for 5 minutes (0.2 group) and a continuous infusion dose of 0.4 µg/kg/hr for 25 minutes after a loading dose of 6 µg/kg/hr for 5 minutes (0.4 group). The recovery process was then observed for 60 minutes post infusion. The tid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
13
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 22 publications
(13 reference statements)
3
13
0
Order By: Relevance
“…Hemodynamic stability was maintained within group D, with similar findings to previous studies. 3,9,12,[14][15][16]20,29 Heart rate decreased significantly compared with propofol during the initial 10minute loading dose and steadily increased once the procedure was initiated. Patients in group P had a decrease in MAP and respiratory rate compared with group D; however, this was not statistically significant.…”
Section: Discussionmentioning
confidence: 99%
“…Hemodynamic stability was maintained within group D, with similar findings to previous studies. 3,9,12,[14][15][16]20,29 Heart rate decreased significantly compared with propofol during the initial 10minute loading dose and steadily increased once the procedure was initiated. Patients in group P had a decrease in MAP and respiratory rate compared with group D; however, this was not statistically significant.…”
Section: Discussionmentioning
confidence: 99%
“…However, sedation may carry a risk of an upper airway obstruction or unconsciousness, when using sedative agents. [14] The accumulation of experiences of dexmedetomidine sedation in such patients is necessary for its safe use.…”
Section: Discussionmentioning
confidence: 99%
“…[89] A comparison of two different doses of dexmedetomidine (0.5 ug/kg and 1 ug/kg) to suppress hemodynamic changes to tracheal intubations showed that the higher dose was more effective when used as bolus. [90]…”
Section: Evidence Based Comparison With Other Drugsmentioning
confidence: 99%